Expanding the geriatric mental health workforce through utilization of non-licensed providers. (2nd September 2017) - Kunik, Mark E.; Mills, Whitney L.; Amspoker, Amber B.; Cully, Jeffrey A.; Kraus-Schuman, Cynthia; Stanley, Melinda; Wilson, Nancy L.
ABSTRACT: Objectives: We evaluate policy and practice strategies for bolstering the geriatric mental healthcare workforce and describe costs and considerations of implementing one approach. Method: Narrative overview of the literature and policy retrieved from searches of databases, hand searches, and authoritative texts. We identified three proposed strategies to increase the geriatric mental healthcare workforce: (1) production of more geriatric mental health providers; (2) team-based care; and (3) non-licensed providers. We evaluate each in terms of challenges and potential and provide estimates of costs, policy, and practice considerations for training, employing, and supervising non-licensed mental health providers. Results: Use of non-licensed providers is key to reforms needed to allow a more older adults to access necessary mental healthcare. Licensed and non-licensed providers have achieved similar improvements for generalized anxiety disorder among patients, although non-licensed providers did so at a lower cost. Conclusion: Supervised non-licensed providers can extend the reach of licensed providers for specific mental health conditions, resulting in lower costs and increased number of patients treated. Although several barriers to implementation exist, policy and infrastructure changes that may support this type of care delivery model are emerging from reforms in financing and associated delivery initiatives created by the Affordable Care Act.